Persistence of Anti-HBs Antibody and Immunological Memory in Healthy Individuals Vaccinated with Hepatitis B Vaccine (Stamford Journal of Microbiology, 2011)
Hepatitis B virus (HBV) infection is one of the major public health problems in the world. It is estimated that there are three hundred million HBV carriers and around one million deaths annually due to HBV infection worldwide. Vaccination is considered to be the best solution to this problem. The present study was conducted to investigate the efficacy of the vaccine administered against hepatitis B and to reveal the immunological memory against the vaccine. Samples were taken from both male (74 individuals) and female (37 individuals) from different age groups ranging from three to sixty three years. Among the population studied, both good (63.06%) and hypo (36.94%) responders were found. All the individuals (100%) showed a satisfactory result having an anti-HBs antibody titer above the protective level (≥ 10 IU/L).DOI: http://dx.doi.org/10.3329/sjm.v1i1.9101  Stamford Journal of Microbiology, Vol.1(1), July 2011, p.37-41